Regression models for the comparison of measurement methods - Bolfarine, Heleno; Springer; de Castro, Mário; Galea, Manuel (2020)
This book provides an updated account of the regression techniques employed in comparing analytical methods and to test the biases of one method relative to others - a problem commonly found in fields like analytical chemistry, biology, engineering, and medicine. Methods comparison involves a non-standard regression problem; when a method is to be tested in a laboratory, it may be used on samples of suitable reference material, but frequently it is used with other methods on a range of suitable materials whose concentration levels are not known precisely. By presenting a sound statistical background not found in other books for the type of problem addressed, this book complements and extends topics discussed in the current literature. It highlights the applications of the presented techniques with the support of computer routines implemented using the R language, with examples worked out step-by-step. This book is a valuable resource for applied statisticians, practitioners, laboratory scientists, geostatisticians, process engineers, geologists and graduate students.
Introduction
Two Methods
Two or More Methods
Model Checking and Influence Assessment
Data Analysis
Miscellaneous Results
R Scripts
Index
Includes bibliographic reference and index
Keywords: Statistics -- Statistics Methods -- Methods (Music)